Relationship between exchange block time in swim starts and final performance in relay races in international championships - Saavedra, J. M.; Garcia-Hermoso, A.; Escalante, Y.; Dominguez, A. M.; Arellano, R.; Navarro, F. (Journal of Sports Sciences, 2014)
The purpose of this study was to investigate the association between relay exchange block time and final performance in 4 × 100-m and 4 × 200-m freestyle and 4 × 100-m medley relays as a function of sex (men and women) and classification (medallists and non-medallists) in international competitions. Nineteen international competitions covering a 13-year period (2000-2012) were analysed retrospectively. The data corresponded to a total of 827 team relay histories (407 men, 420 women). Kruskal-Wallis and Mann-Whitney tests were performed to determine any differences by sex, classification, and event. Similarly, the relationship between the exchange block times and final performance was examined by means of a Pearson correlation analysis. In the three events, the men`s exchange block times were shorter than those of the women (?2 = 0.049-0.109; P < 0.001). The exchange block time was especially relevant for the women`s relay medallists in the 4 × 100-m freestyle (r = 0.306, P = 0.021) and 4 × 100-m medley (r = 0.385, P = 0.011), while for men the relationship was clearer for the non-medallists. These results suggest that the exchange block time should be considered as one of the performance parameters of swimming relay starts, and thus should be included explicitly as part of training. In particular, the coach could design training targeted at standardising an optimal exchange block time equal to or less than that expected for other teams in the competition.